Spatial variability of Cu, Mn and Zn in marginal sandy beach ridges soil - Dharejo, Khalil Ahmed; Abdul Rahim, Anuar; Yusop, Mohd Khanif; Abd. Wahid, Samsuri; Junejo, Nasima (Academic Journals, 2011)
The concentrations of Mn, Cu and Zn in marginal sandy soils were spatially heterogeneous. The objective of presented study were i) to quantify the variability of Mn, Cu and Zn concentration in marginal sandy soil; and ii) to develop the pattern of that variability in kriged maps. The georeferenced soil samples (n = 26) were taken at 0 to 15 and 15 to 30 cm depths from the experimental site located at Telaga Papan Setiu, Terengganu, Peninsular Malaysia. Soil samples were analyzed for extractible Mn, Cu and Zn and spatial variability was quantified with the geostatistics. Co-efficient of variation ranged from 31 to 75% indicating the heterogeneity of Mn, Cu and Zn in soil and spatial ranges varied from 495 to 2110 m in the studied area. The geostatistical analyses showed a definable spatial structure for Mn, Cu and Zn at both the depths. Cross validation test showed accurate interpolation and 26% of the data were positively correlated for Mn, Cu and Zn in the sandy soil. Kriged maps of marginal sandy area indicated that >50% area was high in Mn content at both the depths. Very high content of Mn were found in 6.8 ha of top soil and 9.5 ha of sub soil. Maps for the Zn content showed that >50% area was low at surface and medium at lower depth of sandy soil. Study concluded that quantification of Mn, Cu and Zn variability would assist in planning of future soil sampling as well as site specific management zone based strategies for crop production on these marginal sandy soils.